Bulb growth potential is independent of leaf longevity for the spring ephemeral Erythronium americanum Ker-Gawl - Bertrand, Hugo (Journal of experimental botany, 2023)
© The Author(s) 2022. Published by Oxford University Press on behalf of the Society for Experimental Biology. All rights reserved. For permissions, please email: journals.permissionsoup.com.